Peripheral inflammation over the course of a cognitive behavioral intervention in PTSD - von Majewski, Kristin; Rohleder, Nicolas; Ehring, Thomas (Brain, Behavior, & Immunity-Health, 2023)
Inflammation has an important predictive role for long-term health. This is also true when looking at the specific population of trauma survivors with PTSD. There are emerging findings showing that PTSD is related to reduced somatic health as well as evidence linking inflammation with disease outcomes in this group, such as heart diseases and early mortality, regardless of age, gender or conventional risk factors. The effectiveness of cognitive behavioral therapy for PTSD symptom severity has been demonstrated by several previous studies. In contrast, literature is scarce, yet, whether inflammation improves over the course of treatment for PTSD. Therefore, the aim of this study was to investigate whether not only PTSD symptoms, but also inflammation changes over the course of psychological treatment. Twenty-nine PTSD patients were followed while attending an outpatient clinic receiving cognitive behavioral therapy. Inflammation, determined by the C-reactive protein (CRP) assessed via the dried blood spot (DBS) technique, and symptom severity, surveyed by the PTSD Checklist for DSM-5 (PCL) were measured at 5 points before trauma-focused therapy, as well as after four, eight and twelve weeks of intervention; furthermore, a 10-month follow-up assessment was conducted. Results revealed significant improvements of PTSD symptom severity during investigation, but no significant changes in the inflammatory biomarker (CRP). Results in terms of improvement in PTSD symptom severity are in line with prior findings. The results obtained for inflammation may suggest that risk factors for somatic health consequences in PTSD patients remain despite successful psychological treatment. Further longitudinal studies are needed to fully understand the relationship between inflammation and therapeutic outcome and to develop interventions normalizing inflammation in PTSD patients.
CRIS-Team Scopus Importer:2023-04-28
Keywords: CBT; CRP; Inflammation; Inflammatory biomarker; Posttraumatic stress disorder; Psychological treatment; Trauma